Д. І. ДОНЦОВ: ПОЧАТОК ФОРМУВАННЯ СВІТОГЛЯДУ (Zaporizhzhia Historical Review, 2021)
The article examines formation of the ideology of the well-known Ukrainian figure – Dmytro Ivanovych Dontsov, the theorist of the integral nationalism (1883-1973).